Understanding Poverty in South Africa: Assessing the Twist and Turns of Measurement and Conceptual Misfit - Ndaguba, E.A.; Ijeoma, E.O.C. (Journal of Reviews on Global Economics, 2019)
To fight poverty in South Africa, one must understand the underneath causes, origin, factors and cases that make people fall into and remain in poverty. These the measurement criterion did not take into cognizance establishing a measurement and conceptual parameter for understanding poverty in the African setting. In literature, there are two main arguments to poverty measurement, unidimensional and multidimensional measurement to poverty. However, in a case where both measure seemed to evade inclusiveness, as to reason why poverty has remained transgenerational. We ask, in what ways, could poverty be reduced? What forms the basis of the relief – social grants? What are the conditions that makes people who fall into poverty from affluence remain in poverty in the country? The approach was adopted from Statistic South Africa and over 100 research papers. Results demonstrates that eighteen million individuals are under the social grant system with a population of merely over forty five million people. Millions of households and families are falling into deep poverty, and the social grant system is becoming unsustainable. This paper is a referendum on the need for a new method of understanding poverty and means through which it be approached. It also intends to demonstrate that poverty is not just a mere measure of income or consumption, but unfulfilled desires. With the intent of understanding how government can adequately conceptual poverty, thereby leading to a more realistic approach of poverty reduction.